Targeting Neutrophil Adhesive Events to Address Vaso-Occlusive Crisis in Sickle Cell Patients - Morikis, Vasilios A.; Hernandez, Alfredo A.; Magnani, John L.; Sperandio, Markus; Simon, Scott I. (Frontiers in Immunology, 2021)
Neutrophils are essential to protect the host against invading pathogens but can promote disease progression in sickle cell disease (SCD) by becoming adherent to inflamed microvascular networks in peripheral tissue throughout the body. During the inflammatory response, leukocytes extravasate from the bloodstream using selectin adhesion molecules and migrate to sites of tissue insult through activation of integrins that are essential for combating pathogens. However, during vaso-occulsion associated with SCD, neutrophils are activated during tethering and rolling on selectins upregulated on activated endothelium that line blood vessels. Recently, we reported that recognition of sLex on L-selectin by E-selectin during neutrophil rolling initiates shear force resistant catch-bonds that facilitate tethering to endothelium and activation of integrin bond clusters that anchor cells to the vessel wall. Evidence indicates that blocking this important signaling cascade prevents the congestion and ischemia in microvasculature that occurs from neutrophil capture of sickled red blood cells, which are normally deformable ellipses that flow easily through small blood vessels. Two recently completed clinical trials of therapies targeting selectins and their effect on neutrophil activation in small blood vessels reveal the importance of mechanoregulation that in health is an immune adaption facilitating rapid and proportional leukocyte adhesion, while sustaining tissue perfusion. We provide a timely perspective on the mechanism underlying vaso-occlusive crisis (VOC) with a focus on new drugs that target selectin mediated integrin adhesive bond formation.